Arctic hydroclimate variability during the last 2000 years : current understanding and research challenges - Linderholm, Hans W.; Nicolle, Marie; Francus, Pierre; Gajewski, Konrad; Helama, Samuli; Korhola, Atte; Solomina, Olga; Yu, Zicheng; Zhang, Peng; D'Andrea, William J.; Debret, Maxime; Divine, Dmitry V.; et al. (Climate of the Past)
2018